Differentiated Instruction Content and Process in Learning to Sing Macapat Songs - Hasan, Latif Nur; Pairin, Udjang; Sodiq, Syamsul (Proceeding of International Joint Conference on UNESA, 2025)
Learning to sing Macapat songs has different characteristics from other materials in the Javanese curriculum. It is even different from learning other songs. Each student's various and specific needs to achieve the same goal differentiate it. This is based on the concept of differentiated Instruction. These needs are based on students' interests, preferences, strengths, and struggles. This study aims to describe the different needs in learning Macapat songs and alternative solutions for treating these differences in needs. Grouping these needs can be based on Gender, Ability to sing songs (Advanced, Medium, Beginner), insensitivity to tone, and student learning style. These needs can be grouped based on Gender, Ability to sing songs (Advanced, Medium, Beginner), insensitivity to tone, and student learning styles. Different treatments for each group can be implemented by differentiating content and process.